2011
DOI: 10.1111/j.1349-7006.2011.02140.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor p16INK4a controls oncogenic K‐Ras function in human pancreatic cancer cells

Abstract: Pancreatic cancer is characterized by oncogenic activation of K-Ras and inactivation of the cell cycle inhibitor p16INK4a . We previously demonstrated that reintroduction of p16INK4a reversed anoikis resistance and clonogenicity of human pancreatic cancer cells, properties commonly attributed to the transforming potential of oncogenic K-Ras. Therefore, we aimed to determine the role of Ras after p16INK4a re-expression. Here, we show that restitution of p16INK4a in pancreatic cancer cell lines elicits a profoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…When p16 is actively expressed KRAS activity is downregulated and ERK is not phosphorylated, therefore p-ERK status is dependent on and correlates with p16 status, even in the presence of an activitating KRAS mutation. These data reiterate in ovarian tissues the findings of Rabien and colleagues (56) in pancreatic and colon cancer cells.…”
Section: Ink4amentioning
confidence: 66%
See 1 more Smart Citation
“…When p16 is actively expressed KRAS activity is downregulated and ERK is not phosphorylated, therefore p-ERK status is dependent on and correlates with p16 status, even in the presence of an activitating KRAS mutation. These data reiterate in ovarian tissues the findings of Rabien and colleagues (56) in pancreatic and colon cancer cells.…”
Section: Ink4amentioning
confidence: 66%
“…This study also identified a clear inverse relationship between p-ERK and p16 staining (P ¼ 0.0007, Fisher's Exact Test; Table 4) and a high level of overlap between activating KRAS mutations and p16 loss. Both the lack of correlation between KRAS mutation status and ERK phosphorylation, and the inverse relationship between p-ERK and p16 status can be explained by the negative regulation of KRAS expression and activity by p16 (56). When p16 is actively expressed KRAS activity is downregulated and ERK is not phosphorylated, therefore p-ERK status is dependent on and correlates with p16 status, even in the presence of an activitating KRAS mutation.…”
Section: Ink4amentioning
confidence: 99%
“…Pancreatic adenocarcinomas arise from premalignant pancreatic intraepithelial neoplasia 39. Progression from pancreatic intraepithelial neoplasia to adenocarcinoma results in loss of p16INK4a and thus impaired ability to form senescent cells 40. Carrière et al21 assessed the degree of senescence in pancreatic intraepithelial neoplasia and adenocarcinoma in an activated oncogenic +Kras/-RB mouse model.…”
Section: Cellular Senescence and The Gi Tractmentioning
confidence: 99%
“…About 5-10% of breast cancers are inherited, one-third of which are caused by dominant BRCA-gene mutations (Xu et al, 2011). Research has previously focused on the protein-coding genes such as oncogenes, tumor suppressor genes, DNA repair genes, and anti-metastatic genes in cancer genetics (Jacob & Praz , 2002;Rabien et al, 2011).…”
Section: Introductionmentioning
confidence: 99%